Strategi Pengembangan Dosen Perguruan Tinggi Kaitannya Dengan Profil Dosen Yang Produktif - Tita Meirina Djuwita (PUBLICA, 2011)
A professional lecturer is the one who determine what is good for students based on professional considerations. The high and low quality of academic education in higher education is depending on the degree of professionals owned by the lecturer. The existence of this thing has caused many education institutions to race each other to enhance the performance of lecturers and require them to maximum their potentials and skills in performing their duties. The efforts to develop the lecturer need to be put in a planned and sustained activity in order to fulfill the demand and the need of quality standard that has changed and developed from time to time. In an attempt to improve the performance of lecturers in universities, then it requires criteria or characteristics of lecturers that professional in performing their duty and finally can show themselves as the productive lecturer.